Oh, what a happy little math problem we have here! To find the product of 3x cubed and 2x squared, we simply multiply the coefficients (3 and 2) to get 6, and then add the exponents of x (3 + 2) to get x to the power of 5. So, the answer is 6x to the power of 5. Isn't that just a beautiful equation?
the derivative of 3x is 3 the derivative of x cubed is 3 times x squared
Since you add up the 'x''s (i.e. (2x) (3x) (4x) = 24x cubed) 6x2
Your question is ambiguous. (3x)^3 times (3x)^3 = 27x^3 times 27x^3 = 729x^6 or, if you meant 3x^3 times 3x^3 = 9x^6
(5x 2 - 8x + 1) + (2x 2 - 4x - 11)
the answer is (3x-2)(9x squared+6x+4)
This is impossible as the variables are different
6x3 + 9x2 - 2x2 - 3x Before any grouping, take out the common factor, x, to give x*(6x2 + 9x - 2x - 3) = x*[3x*(2x + 3) - 1*(2x + 3)] = x*(2x + 3)*(3x - 1)
5x3 - 3x2 + 2x = x*(5x2 - 3x + 2) The quadratic has no real factors.
2x squared - 3x
the derivative of 3x is 3 the derivative of x cubed is 3 times x squared
x(3x - 2)
5
Since you add up the 'x''s (i.e. (2x) (3x) (4x) = 24x cubed) 6x2
3x2-2x-8 = (3x+4)(x-2) when factored
6x2 + 10x = 2x*(3x + 5)
If the equation is (2x)^3-3x, then the answer is -985. However, if the equation if 2(x)^3-3x, then the answer is -235.
Oh, dude, that's like basic math, right? So, 2x squared plus x squared is just 3x squared. It's like adding apples to apples, but with math. Easy peasy lemon squeezy!